Pendampingan KSM Matematika dan IPA Integrasi Agama untuk Madrasah Ibtidaiyah di MI Mazraatul Ulum 02 Paciran Lamongan - Eny Latifah; Nurul Hidayati (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2021)
The Madrasa Science Competition is a competition intended to comprehensively improve multi-education through a culture of learning, creativity and motivation in achieving the best achievements by upholding sportsmanship and Islamic religious values. The purpose of this assistance is to provide guidance and direction on the subject of Mathematics and IPA of Religion Integration at the Madrasah Science Competition (KSM) at the Madrasah Ibdidaiyah level Mazra’atul Ulum 02 Paciran Lamongan. There are three (3) stages in this mentoring: preparation, implementation and evaluation. The results of the assistance show: (1) Increased interest in student competition, (2) Increased Mastery of Mathematics and IPA Integration of Religion Materials, (3) Increased scores on evaluation of the material of Mathematics and IPA of Integration of Religion.